Violence Against Women and the Role of Welfare Reform in Stanislaus and Kern Counties, California, 1999-2002 - Goodwin, Sandra Naylor ([Verlag nicht ermittelbar], 2005)
This study investigated the relationship between domestic violence and welfare reform. Two specific goals were (1) to determine the impact of domestic violence on welfare tenure and employment over a three-year period, and (2) to examine the well-being of children of female welfare recipients who experienced domestic violence. In addition, the study examined issues related to mental health problems and alcohol and drug problems, both of which are associated with domestic violence. This study was based on three rounds of interviews with a random sample of welfare recipients in Kern and Stanislaus Counties, California, between April 1999 and December 2002. Although the interview instrument was slightly altered for each round, the questions in all three rounds focused on employment history, health, mental health, domestic violence victimization, children's well-being, and alcohol and drug use.